Ascocotyle longa (Digenea: Heterophyidae) infecting dolphins from the Atlantic Ocean - Ebert, Mariana Bertholdi [UNESP] (2021)
We report for the first time the infection of dolphins with Ascocotyle longa found in the intestines of three different species, Sotalia guianensis, Steno bredanensis, and Tursiops truncatus gephyreus, which were found washed ashore along the southeastern and southern Brazilian coast. The worms were identified based on morphological and molecular data using the 28S rDNA gene and the COI gene. Specimens of A. longa from the pinniped Otaria flavescens were also analyzed. As the first isolation of A. longa from cetaceans, the present study increases the distribution area and range of definitive hosts of this trematode, and provides new molecular data to complement the phylogeny of the group in future studies, thus contributing to the scientific knowledge of this potentially zoonotic parasite.